Integration of lipidomics and widely targeted metabolomics provides a comprehensive metabolic landscape of Poa pratensis under cadmium stress - Ting Cui; Yong Wang; Kuiju Niu; Chunxu Zhao; Huiling Ma (BMC Plant Biology)
Abstract Background Soil cadmium (Cd) contamination poses significant environmental challenges globally. Kentucky bluegrass is considered a viable plant for remediating Cd-contaminated soils due to its high tolerance to Cd and accumulation capacity. Yet, the complete metabolic landscape underlying Cd detoxification mechanisms of Kentucky bluegrass remains incompletely understood. Results Here, widely targeted metabolomics was used to identify key metabolites of Kentucky bluegrass that were responsive to Cd stress in comparisons between Cd-resistant (M) and sensitive (R) varieties. Moreover, lipidomics analyses were used to assess the content, composition, and saturation levels of lipid molecular species. The M variety exhibited higher levels of free amino acids, saccharides, and flavonoids (flavones, flavonols, isoflavones, and flavanones) after Cd stress that likely enhance its tolerance to Cd stress. Within the M variety, 183 lipid species (81%) were less abundant after Cd stress, representing a much larger number than the 81 lipid species (41.54%) similarly less abundant in the R variety. The lipid species with increased abundances primarily comprised diacylglycerols, monogalactosyldiacylglycerol, phosphatidylcholine, triacylglycerol, and lysophosphatidylcholine that exhibited higher saturation levels. Conversely, the lipid species with decreased abundances largely comprised those with shorter acyl chains including free fatty acids, phosphatidic acid, and lysophosphatidic acid, as well as those with higher unsaturation levels, including phosphatidylglycerol, diacylglycerol, triacylglycerol, phosphatidylcholine, and lysophosphatidylcholine. The elongation of these lipid acyl chains under Cd stress contributes to the increased membrane thickness and rigidity in Kentucky bluegrass, resulting from the dense packing of hydrophobic tails and enhanced lipid-lipid interactions. The changes in these metabolites and lipids may play a significant role in enhancing Cd tolerance, distribution, and accumulation in Kentucky bluegrass. Conclusion The results of this study provide a comprehensive metabolite profile for Kentucky bluegrass in response to Cd stress, elucidating the key metabolite characteristics essential for Cd detoxification under Cd-induced stress. Furthermore, the results provide insights into the metabolic regulation of metabolites and lipid homeostasis that contribute to enhanced Cd tolerance in Kentucky bluegrass.